Pathologically Complete Response to Camrelizumab and Apatinib in Advanced Cervical Cancer with PTEN, PIK3CA, MTOR, and ARID1A Mutations: A Case Report - Zhi-Ping Liu; Si-Han Liu; He Zhao; Fang-Ying Ruan; Da-Xin Zhang; Bai Xu (Case Reports in Oncology)
Introduction: Limited treatment options are available for residual locally advanced cervical cancer after concurrent radio-chemotherapy. Pembrolizumab has been approved by the US Food and Drug Administration to treat patients with persistent, recurrent, and metastatic cervical cancer. However, it is expensive and not covered by medical insurance in China. Case Description: A patient presented with stage IIIC1 cervical cancer characterized by PTEN, PIK3CA, MTOR, and ARID1A mutations, accompanied by low programmed cell death-ligand 1 expression (tumor cell proportion score 1% and combined positive score 1). The patient exhibited a residual cervical lesion after concurrent radio-chemotherapy but eventually achieved a pathologically complete response through a combination of the programmed cell death-1 (PD-1) inhibitor camrelizumab with the antiangiogenic drug apatinib (two medicines produced by Chinese Jiangsu Hengrui Pharmaceutical Co.). Surgical intervention confirmed the lack of residual tumor cells in the cervix. Regular follow-up confirmed that disease-free survival time was 41 months and overall survival time was 51 months. Adverse events, including cutaneous capillary endothelial proliferation, hepatic insufficiency, hemorrhoidal hemorrhage, and neutropenia, were manageable during treatment with camrelizumab and apatinib. Conclusion: Our findings suggest that the combination of camrelizumab and apatinib could offer a valuable therapeutic option for residual advanced cervical cancer patients after concurrent radio-chemotherapy. Camrelizumab is affordable, at just 10% of the price of pembrolizumab, although it is similarly not covered by medical insurance for cervical cancer in China. The PTEN, PIK3CA, MTOR, and ARID1A gene mutations hold the potential to serve as predictive biomarkers for cervical cancer patients treated by PD-1 inhibitors.